The Impact of Role Conflict Originating from Mid-Level Manager Actions on Intention to Leaving the Job and Performance - Şükran Gökce; Ahmet Diken; Ümran Münire Kahraman (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This study aims to reveal the effect of role conflict and role ambiguity arising from mid-level manager actions on the turnover intension and job performance. Another aim of the study is to contribute to the limited literature available on med-level management and managers especially in our country through the variables examined. A survey-based method was used in the study. The prepared questionnaire was sent to academic and administrative staff working as mid-level managers at two public universities. The item form used in the study was created by bringing together questions from different scales. The explanatory factor analysis was applied to investigate the construct validity and the factor structure of the items was revealed. Alpha model was used to determine the reliability of the scale. No significant evidence has been found as to whether the actions of mid-level managers interacting with many units and person due to their position in the organization will affect the role conflict. For role ambiguity, as claimed in the study hypothesis, mid-level manager actions have an increasing effect on role uncertainty. In the third and fourth hypothesis of the study, the effect of role conflict on the turnover intention and organizational performance, respectively, was investigated. Accordingly, role conflict positively affects turnover intention. However, there is no significant evidence for the effect of role conflict on performance. It is an interesting finding that the role conflict has no direct effect on performance as a result of the research. The implication is that to improve business performance, it is necessary to be informed about mid-level manager actions before reducing role conflict. Because reducing role conflict does not directly increase performance. Role ambiguity positively affects to turnover intension; it affects business performance negatively. It has been demonstrated that the role conflict and role ambiguity increased the turnover intention, while the increasing turnover intention has turned into behavior, resulting in an increase in the turnover rate, which is the result of absenteeism and walk-out. The loss of individuals, who are shown as the strategic source of today's organizations, will add extra costs to the organization. In this sense, in order to eliminate or reduce the negative consequences of role conflict and role ambiguity, it is very important to use communication channels within the organization at the maximum level, to include clear expressions in the given messages, and to bring the mid-level managers as close as possible to the decision-making processes